Closed-loop Artificial Pancreas Development: A Review - Glumcevic, Sabina; Masetic, Zerina; Viteskic, Benjamin (2023 46th MIPRO ICT and Electronics Convention (MIPRO), 2023)
Diabetes is a widespread disease, suffered by millions, including children. Treatment of diabetes type 1 and sometimes even type 2, entails multiple blood glucose checks and insulin injections per day, and can thus be extremely exhausting, especially for very young children. Open-loop systems of insulin delivery, insulin pumps, used today commercially, require human interaction which can lead to low blood glucose control due to human mistakes. Fully automated closed-loop systems of artificial pancreas, as one-hormone as well as dual-hormone systems, are being developed. This paper is the literature survey of the latest research on the automated closed-loop artificial pancreas. The objective of this paper is to explore the development of devices and techniques to facilitate the daily life of diabetic patients with emphasis on the latest research on the topic. From so-called pens to open-loop systems of insulin pumps, closed-loop systems with user interaction -hybrid closed-loop, to the latest fully automatized closed-loop -artificial pancreas. In total 300 articles are reviewed from which 150 articles are retained for the literature survey and 50 are analysed in this literature review.